2008
DOI: 10.1093/annonc/mdn287
|View full text |Cite
|
Sign up to set email alerts
|

Non-thromboembolic pulmonary hypertension in multiple myeloma, after thalidomide treatment: A pilot study

Abstract: Preexisted endothelial dysfunction due to structural cardiac disease enhances the vasoactive substances release causing increased pulmonary vascular resistance. Thalidomide possibly causes a vasodilator and vasoconstriction imbalance, which may cause abnormal pulmonary vascular response interfering to a vicious circle perpetuating PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…PH in the absence of thromboembolic events has also been described in 3 patients with MM during thalidomide treatment [5, 6, 7] and in a pilot study [1]. We also experienced occurrence of PH in a MM patient during treatment with thalidomide.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…PH in the absence of thromboembolic events has also been described in 3 patients with MM during thalidomide treatment [5, 6, 7] and in a pilot study [1]. We also experienced occurrence of PH in a MM patient during treatment with thalidomide.…”
Section: Introductionsupporting
confidence: 65%
“…Furthermore, in the pilot study of Lafaras et al [1], 4 of the 82 treated patients had PH and improved after discontinuation of therapy. Our patient showed clinical and echocardiographic signs of PH after a few days of thalidomide therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, carfilzomib has been associated with a rate of PH of approximately 3%, with 1% of patients having severe PH. 32 Patient 3 was treated with numerous chemotherapeutic agents, including carfilzomib both before and after PH was detected (Table 2).…”
Section: Treatment-related Vasculopathymentioning
confidence: 99%
“…This outcome suggests a possible association between MM and PH. In addition, Lafaras et al reported that some MM patients receiving thalidomide develop non-thromboembolic PH (21). Therefore, lenalidomide, not thalidomide, was chosen as the third drug in the combination therapy used in this case, in which the patient had severe PH.…”
Section: Introductionmentioning
confidence: 98%